(untitled) - Bock, Darrell L. (Michigan, U.S.A, 2016)
This clear, compact introduction surveys what the Gospels tell us about who Jesus is by exploring his teachings and actions in their contexts. Darrell Bock, a leading evangelical New Testament scholar who speaks and teaches around the world, and Benjamin Simpson treat the Gospels as reliable sources for a plausible portrait of Jesus. Condensing years of extensive study on the topic, this handy, readable textbook presents fresh ways to understand the Gospels, especially the Synoptics in comparison with John.
Keywords: Jesus Christ